Interaction of Colchicine-Site Ligands With the Blood Cell-Specific Isotype of β-Tubulin—Notable Affinity for Benzimidazoles - Montecinos, Felipe; Loew, Maura; Chio, Tak I.; Bane, Susan L.; Sackett, Dan L. (Frontiers in Cell and Developmental Biology, 2022)
Tubulin, the main component of microtubules, is an α-β heterodimer that contains one of multiple isotypes of each monomer. Although the isotypes of each monomer are very similar, the beta tubulin isotype found in blood cells is significantly divergent in amino acid sequence compared to other beta tubulins. This isotype, beta class VI, coded by human gene TUBB1, is found in hematologic cells and is recognized as playing a role in platelet biogenesis and function. Tubulin from the erythrocytes of the chicken Gallus gallus contains almost exclusively βVI tubulin. This form of tubulin has been reported to differ from brain tubulin in binding of colchicine-site ligands, previously thought to be a ubiquitous characteristic of tubulin from higher eukaryotes. In this study, we sought to gain a better understanding of the structure-activity relationship of the colchicine site of this divergent isotype, using chicken erythrocyte tubulin (CeTb) as the model. We developed a fluorescence-based assay to detect binding of drugs to the colchicine site and used it to study the interaction of known colchicine-site drugs with CeTb. Among the ligands known to bind at this site, most colchicine derivatives had lower affinity for CeTb compared to brain tubulin. Remarkably, many of the benzimidazole class of ligands shows increased affinity for CeTb compared to brain tubulin. Because the colchicine site of human βVI tubulin is very similar to that of chicken βVI tubulin, these results may have relevance to the effect of anti-cancer agents on hematologic tissues in humans.